Validity and reliability of creative thinking skills assessment instruments in mathematics subjects for elementary school - Tumangger, Mia Hafizah; Cahyaningrum, Ryzka; Maghfiroh, Anik; Sahrul (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Creative thinking is an essential skill that needs to be developed from an early age. The absence of valid and reliable instruments poses major challenges in identifying and enhancing students’ creative thinking skills in elementary school mathematics learning. This study aimed to evaluate the validity and reliability of a creative thinking assessment instrument for elementary school mathematics subjects. A quantitative approach was employed with five expert validators and 150 research participants selected through total sampling. The research instruments included expert validation sheets and a creative thinking assessment instrument for elementary mathematics. Data were analyzed using several methods: Aiken’s V for content validity, Rasch model analysis for dimensionality, Confirmatory Factor Analysis (CFA) for construct validity, Ebel’s formula for inter-rater reliability, and Cronbach’s Alpha for internal consistency reliability. The results showed that the creative thinking assessment instrument was valid and reliable, indicating that it can be used as an accurate measurement tool to identify students’ creative thinking skills. The findings of this study serve as a valuable reference for educators in evaluating creative thinking and provide a foundation for developing more innovative learning strategies in mathematics education.